The Impact of The Quarter Life Crisis on Turnover Intention in The Digital Era - Putu Aninditha Cahya Utami; Luh Putu Mahyuni (Green Publisher Indonesia, 2025)
This study aimed to determine the impact of the quarter-life crisis on turnover intention in the digital era, as well as to identify strategies for reducing turnover intention caused by the quarter-life crisis. The population of this research consisted of young adults holding strategic positions in companies in Denpasar City. A qualitative research method with in-depth interviews with 10 informants was used to explore the effects of the quarter-life crisis on turnover intention in the digital era occurring in Denpasar City. The results of the study showed that young adults viewed self-branding behavior on social media as a positive thing as long as it was not overdone. The desire to resign from a company was more likely to arise when individuals felt they were unsuccessful in leading a team, did not align with the company’s leadership, or faced excessive work pressure in terms of workload and working hours. The effects of feeling pressured or other factors within the quarter-life crisis dimensions that drive young adults to want to leave the company must immediately be addressed to find solutions to mitigate them.